Effects of ropinirole prolonged-release on sleep disturbances and daytime sleepiness in Parkinson disease - Dusek, Petr; Busková, Jitka; Růzicka, Evzen; Majerová, Veronika; Srp, Antonín; Jech, Robert; Roth, Jan; Sonka, Karel (Clinical neuropharmacology, 2010)
This study evaluated the effects of ropinirole prolonged-release (RPR) in comparison with ropinirole immediate-release (RIR) on sleep-related disorders in Parkinson disease (PD).Thirty-three PD patients (aged 62.5 [SD, 8] years; PD duration, 9 [SD, 4] years) were evaluated on a stable dose of RIR and 5 to 13 weeks after switch to the closest possible dose of RPR. The following questionnaires were administered: Epworth Sleepiness Scale, PD Sleep Scale, Pittsburgh Sleep Quality Index, REM Sleep Behavior Disorder Screening Questionnaire, and PD Questionnaire 39. We further monitored the occurrence of restless legs syndrome and sleep attacks (SAs). Motor disability was evaluated by PD diary and by Unified Parkinson Disease Rating Scale part 3 on medication (ON) and after medication withdrawal (OFF). In 8 patients with marked subjective sleep disturbance, polysomnography, and multiple sleep latency test were performed.After switching to RPR, there was an improvement in PD Sleep Scale (94.9 [SD, 23] vs 102.2 [SD, 27]; P < 0.05 corrected), Pittsburgh Sleep Quality Index (7.2 [SD, 3] vs 5.8 [SD, 3]; P < 0.05 corrected), Epworth Sleepiness Scale (14.1 [SD, 5] vs 12.0 [SD, 6]; P < 0.05 corrected) and Unified Parkinson Disease Rating Scale part 3 in the ON state (20.9 [SD, 10] 10 vs 17.6 [SD, 10]; P < 0.05 corrected). Thirteen patients reported disappearance of SAs on RPR. Polysomnography and multiple sleep latency test showed no changes in a subgroup of 8 patients after the switch to RPR.Ropinirole prolonged-release compared with RIR improved subjective quality of sleep, reduced daytime sleepiness, and led to disappearance of SAs in some patients possibly due to a more stable plasma level of ropinirole.
Keywords: indoly; Humans; Dopamine Agonists; Indoles; lidé středního věku; Delayed-Action Preparations; Quality of Life; Dose-Response Relationship, Drug; Female; Aged; dospělí; Psychiatric Status Rating Scales; senioři; lidé; Sleep Wake Disorders; kvalita života; agonisté dopaminu; Antiparkinson Agents; Adult; ženské pohlaví; psychiatrické posuzovací škály; Male; Middle Aged; antiparkinsonika; léky s prodlouženým účinkem; poruchy spánku a bdění; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; Parkinson Disease; Parkinsonova nemoc